A novel dense granule protein, GRA41, regulates timing of egress and calcium sensitivity in Toxoplasma gondii. (17th May 2017) - LaFavers, Kaice A.; Márquez‐Nogueras, Karla M.; Coppens, Isabelle; Moreno, Silvia N. J.; Arrizabalaga, Gustavo
Summary: Toxoplasma gondii is an obligate intracellular apicomplexan parasite with high seroprevalence in humans. Repeated lytic cycles of invasion, replication, and egress drive both the propagation and the virulence of this parasite. Key steps in this cycle, including invasion and egress, depend on tightly regulated calcium fluxes and, although many of the calcium‐dependent effectors have been identified, the factors that detect and regulate the calcium fluxes are mostly unknown. To address this knowledge gap, we used a forward genetic approach to isolate mutants resistant to extracellular exposure to the calcium ionophore A23187. Through whole genome sequencing and complementation, we have determined that a nonsense mutation in a previously uncharacterised protein is responsible for the ionophore resistance of one of the mutants. The complete loss of this protein recapitulates the resistance phenotype and importantly shows defects in calcium regulation and in the timing of egress. The affected protein, GRA41, localises to the dense granules and is secreted into the parasitophorous vacuole where it associates with the tubulovesicular network. Our findings support a connection between the tubulovesicular network and ion homeostasis within the parasite, and thus a novel role for the vacuole of this important pathogen.